Morphology of melt-crystallized β′ phase crystals of monodisperse poly(9, 9-dioctylfluorene). (1st May 2015) - Liu, Jian; Wang, Qilin; Liu, Chengfang; Tian, Hongkun; Geng, Yanhou; Yan, Donghang
Abstract: A novel β′ phase crystal with lamellar structure of monodisperse poly(9, 9-dioctylfluorene) (PFO) has been prepared by means of melt crystallization, demonstrating similar optical properties with β phase crystals. A preliminary determination of unit cell dimensions and molecular packing (orthorhombic, a = 1.30 nm, b = 2.22 nm, c = 3.36 nm, 4 chains, with space group Pmc21 and density 1.06 g/cm 3 ) was made by combined analysis of the selected-area electron diffraction (SAED) and X-ray diffraction (XRD) patterns. In the lamellar crystals, the molecular backbone chains are parallel to the lamellar plane with the alkyl side chains interdigitation in the thickness of lamella. Graphical abstract: Highlights: A novel β′ phase crystal of monodisperse PFO was prepared by melt crystallization. The β′ phase crystal has lamellar structure. The unit cell parameters and space group of β′ phase were given. The β′ phase crystals are more thermal stable than the β phase crystals.